“They don’t have the history and the stature:” examining perceptions of Caribbean offshore medical schools held by Canadian medical education stakeholders - Morgan, Jeffrey; Crooks, Valorie; Snyder, Jeremy; Pickering, John (Canadian Medical Education Journal, 2018)
Background: Caribbean offshore medical schools are for-profit, private institutions that provide undergraduate medical education to primarily international students, including from the United States or Canada. Despite the growing role that offshore medical schools play in training Canadian physicians, little is known about how these institutions are perceived by those in professional and decision-making positions where graduates intend to practice. Methods: The authors interviewed 13 Canadian medical education stakeholders whose professional positions entail addressing the medical education system or physician workforce. Participants were employed in academic, governmental, and non-governmental organizations in leadership roles. Results: Thematic analysis revealed three cross-cutting perceptions of offshore medical schools: (a) they are at the bottom of an international hierarchy of medical schools; (b) they are heterogeneous in quality of education and student body; and (c) they have a unique business model, characterized by profit-generating and serving international students. Conclusion: Consistent growth of the offshore medical school industry in the Caribbean may result in adverse reputational harms for well-established offshore or regional medical schools. Both comparative (e.g., USMLE pass rate) and intuitive factors (e.g., professional familiarity) informed participants’ perceptions. Participants believed that core principles of social accountability in medical education are incompatible with the offshore medical school model.